"Whalecraft": Clifford Warren Ashley and Whaling Craft Culture in Industrial New Bedford. (2nd September 2018) - Williams, Nicole J.
Abstract: This essay considers how New Bedford native Clifford Warren Ashley (1881–1947) shaped a lasting image of America's vanishing whaling industry as a preindustrial craft practice, informed by the Arts and Crafts movement and by the social and environmental toll of industrialization in the city's burgeoning textile mills circa 1900, when New Bedford became one of the nation's leading producers of cotton goods. Focusing on Ashley's influential work as a maritime artist, writer, and designer of period rooms at the Jonathan Bourne Whaling Museum (now the New Bedford Whaling Museum), it explores the range of strategies he adopted to promote whaling's fading traditions of handiwork, including knotting, sailmaking, coopering, shipsmithing, and carving scrimshaw. While Ashley's representations of the great days of the whaling ships mounted a critique of the city's machine-based production, it also obscured whaling's unsavory, proto-industrial character. The whaleship was a crucible of capitalist abuse, alienated labor, and the unstable social relations that came to characterize New Bedford's factory life in the early twentieth century. Whaling also literally fueled the growth of the factory system by furnishing the whale and sperm oils used to lubricate heavy and high-speed machinery. Although Ashley's craftsmen seemed to occupy a simpler, preindustrial past, whaling actually presaged and produced sweeping changes in the nation's modes of production and systems of labor.